Biochemical Preparation of Cell Extract for Cell-Free Protein Synthesis without Physical Disruption - Fujiwara, Kei; Doi, Nobuhide (PLOS ONE, 2016)
Cell-free protein synthesis (CFPS) is a powerful tool for the preparation of toxic proteins, directed protein evolution, and bottom-up synthetic biology. The transcription-translation machinery for CFPS is provided by cell extracts, which usually contain 20–30 mg/mL of proteins. In general, these cell extracts are prepared by physical disruption; however, this requires technical experience and special machinery. Here, we report a method to prepare cell extracts for CFPS using a biochemical method, which disrupts cells through the combination of lysozyme treatment, osmotic shock, and freeze-thaw cycles. The resulting cell extracts showed similar features to those obtained by physical disruption, and was able to synthesize active green fluorescent proteins in the presence of appropriate chemicals to a concentration of 20 μM (0.5 mg/mL).